Lithium secondary battery

By using a combination of silicon-based negative electrode and a single-particle positive electrode active material with a specific content in lithium secondary batteries, the weight ratio is adjusted, and the problems of resistance difference, cracking of active material and gas generation are solved, and better capacity characteristics, fast charging performance and cycle characteristics are achieved.

CN119547219APending Publication Date: 2025-02-28LG ENERGY SOLUTION LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380056498.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-12-22
Filing Date
2023-12-26
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

When using silicon-based negative electrodes and single-particle positive electrode active materials, lithium secondary batteries have problems with resistance differences, cracking of active materials and gas generation, which affects their capacity characteristics, fast charging performance and cycle characteristics.

Method used

A positive electrode composition containing a silicon-based negative electrode and a single-particle positive electrode active material with a specific content is adopted, and the composition and content of the positive electrode are optimized to reduce resistance and gas generation by adjusting the weight ratio of the silicon-based active material and the single-particle active material.

Benefits of technology

It effectively solves the resistance problem of lithium secondary batteries, reduces rupture in high-voltage batteries, reduces gas generation, and improves the cycle performance and life characteristics of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119547219A_ABST
    Figure CN119547219A_ABST
Patent Text Reader

Abstract

The present application relates to a lithium secondary battery comprising a positive electrode, a silicon-based negative electrode, a separator provided between the positive electrode and the negative electrode, and an electrolyte, characterized in that a secondary particle positive electrode active material and a single-particle positive electrode active material are mixed in the positive electrode, and the proportion of the single-particle positive electrode active material is adjusted, and in particular, the ratio of the single-particle positive electrode active material to the secondary particle positive electrode active material is adjusted. The weight ratio of the silicon-based active material of the silicon-based negative electrode used as the counter electrode to the single-particle positive electrode active material is adjusted with respect to the capacity loading amount of the positive electrode active material layer composition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application claims priority to and the benefit of Korean Patent Application Nos. 10-2022-0186055 and 10-2022-0186066 filed in the Korean Intellectual Property Office on December 27, 2022, the entire contents of which are incorporated herein by reference.

[0002] The present application relates to a lithium secondary battery. Background Art

[0003] As a part of the increasing demand for the use of alternative or clean energy due to the rapid increase in the use of fossil fuels, the most active research field is the field of power generation and storage using electrochemical reactions.

[0004] Currently, secondary batteries are a representative example of electrochemical devices utilizing such electrochemical energy, and their use range tends to be gradually expanded.

[0005] With the development of technology and the growth of demand for mobile devices, the demand for secondary batteries as energy sources has grown rapidly. Among such secondary batteries, lithium secondary batteries with high energy density and voltage, long cycle life and low self-discharge rate have been commercialized and widely used. In addition, as such high-capacity lithium secondary battery electrodes, methods for manufacturing high-density electrodes with higher energy density per unit volume are being actively studied.

[0006] Typically, a secondary battery comprises a positive electrode, a negative electrode, an electrolyte and a separator. The negative electrode comprises a negative electrode active material that embeds and deintercalates lithium ions from the positive electrode. As a negative electrode material, carbon-based materials such as graphite have excellent stability and reversibility, but there are limitations in terms of capacity. Therefore, in the field of high capacity, attempts to use Si-based materials with high theoretical capacity as negative electrode materials are increasing.

[0007] That is, lithium secondary batteries are usually manufactured by using compounds embedded with lithium, such as LiCoO2 or LiMn2O4, for the positive electrode and materials not embedded with lithium, such as carbon or silicon materials, for the negative electrode. During charging, the lithium ions embedded in the positive electrode move to the negative electrode through the electrolyte. During discharge, the lithium ions move back to the positive electrode from the negative electrode. During charging, the lithium moving from the positive electrode to the negative electrode reacts with the electrolyte, thereby forming a passivation film, i.e., a solid electrolyte interface (SEI), on the surface of the negative electrode. SEI inhibits the migration of electrons required for the reaction of the negative electrode with the electrolyte, thereby preventing the electrolyte from decomposing, thereby stabilizing the structure of the negative electrode. On the other hand, the formation of SEI is irreversible, resulting in the consumption of lithium ions. That is, the lithium consumed due to the formation of SEI will not return to the positive electrode during the subsequent discharge process, resulting in a decrease in the capacity of the battery.

[0008] On the other hand, in order to improve the performance of lithium secondary batteries, it is necessary to develop technologies that accelerate the charging rate. In order to quickly charge lithium secondary batteries, the migration rate of lithium ions should be fast during the process of lithium ion embedding into the negative electrode. Therefore, battery design is being carried out to shorten the diffusion distance of lithium by forming a negative electrode active material layer with a thickness at the film level, and to increase the conductivity by forming a carbon coating layer on the surface of the negative electrode active material layer, thereby reducing the internal resistance, thereby achieving high output.

[0009] In order to ensure such fast charging performance and energy density, attempts to use silicon-based negative electrodes to replace existing carbon-based (graphite) negative electrodes are increasing. That is, in order to improve performance, the content of silicon-based active materials should be increased in the silicon-based negative electrode. However, if the content of the silicon-based negative electrode is simply increased, various problems such as resistance and volume expansion will occur.

[0010] Regarding the above problems, the resistance problem can be solved by increasing the content of silicon-based active materials and applying secondary particle positive electrode active materials to the positive electrode at the same time. However, the reaction potential of the silicon-based negative electrode is about 0.05V higher than that of the carbon-based negative electrode, so the silicon-based negative electrode is exposed to a high potential. In addition, due to the rupture at high voltage, the gas generation problem arises again. Therefore, the application of single-particle positive electrode active materials as positive electrode active materials has been studied. However, when a single-particle positive electrode active material is used alone, the negative electrode no longer works due to the increased use of the bottom of the silicon-based negative electrode, resulting in poor cycle characteristics.

[0011] Ultimately, for lithium secondary batteries that use silicon-based negative electrodes to achieve capacity characteristics, high energy density, and fast charging performance and use NCMA-based or NCM-based positive electrodes as counter electrodes, it is necessary to continue research on lithium secondary batteries that can reduce resistance differences and solve the problems of active material cracking and gas generation in high-voltage batteries.

[0012] Prior art documents

[0013] (Patent Document 1) Japanese Patent Application Publication No. 2009-080971 Summary of the invention

[0014] Technical issues

[0015] As a result of the study of the above problems, it was found that the capacity characteristics and fast charging performance can be ensured by using a silicon-based negative electrode, and when a single-particle positive electrode active material is used as the positive electrode, the amount of gas generated can be controlled. In particular, it was found that when the single-particle positive electrode active material is mixed with the secondary particle positive electrode active material instead of including the single-particle positive electrode active material alone, and the weight ratio of the silicon-based active material and the single-particle active material is adjusted compared to the capacity loading of the positive electrode, the above problems can be solved.

[0016] Therefore, the present application relates to a lithium secondary battery including a silicon-based negative electrode and a positive electrode containing a single-particle positive electrode active material having a specific content.

[0017] Technical Solution

[0018] An exemplary embodiment of the present specification provides a lithium secondary battery, including a positive electrode; a silicon-based negative electrode; a separator disposed between the positive electrode and the negative electrode; and an electrolyte, wherein the positive electrode includes a positive electrode current collector layer and a positive electrode active material layer disposed on one surface or both surfaces of the positive electrode current collector layer and containing a positive electrode active material layer composition, wherein the silicon-based negative electrode includes a negative electrode current collector layer and a negative electrode active material layer disposed on one surface or both surfaces of the negative electrode current collector layer and containing a negative electrode active material layer composition, wherein the negative electrode active material layer composition includes a silicon-based active material, and the silicon-based active material includes one or more selected from the group consisting of SiOx (x = 0), SiOx (0 < x < 2), SiC, and Si alloy, wherein the positive electrode active material layer composition includes a positive electrode active material containing one or more selected from the group consisting of a secondary particle positive electrode active material and a single-particle positive electrode active material, wherein the positive electrode active material includes one or more selected from the group consisting of nickel, cobalt, manganese, and aluminum, and contains 50 mol% or more of nickel among all metals other than lithium, wherein based on 100 parts by weight of the positive electrode active material, the content of the single-particle positive electrode active material is 1 part by weight or more and 50 parts by weight or less, wherein the capacity loading amount of the positive electrode active material layer composition is 2 mAh / cm 2 or more and 5 mAh / cm 2 or less, and wherein based on 100 parts by weight of the silicon-based active material, the content of the single-particle positive electrode active material is 0.01 part by weight or more and 4 parts by weight or less.

[0019] Advantageous Effects

[0020] The lithium secondary battery according to the present application can ensure that the battery has a high capacity and high energy density by using the silicon-based negative electrode, and can also form a negative electrode thickness at the thin film level by using a silicon-based active material with excellent capacity characteristics, thereby ensuring fast charging performance.

[0021] As the positive electrode, that is, the counter electrode used in this case, the lithium secondary battery according to the present application uses a mixture of the secondary particle positive electrode active material and the single-particle positive electrode active material in the positive electrode, and simultaneously adjusts the ratio of the single-particle positive electrode active material. In particular, the secondary battery according to the present application is characterized in that the weight ratio of the silicon-based active material of the silicon-based negative electrode used as the counter electrode and the single-particle positive electrode active material is adjusted compared to the capacity loading amount of the positive electrode active material layer composition.

[0022] Therefore, the main feature of the present application is to optimize the composition and content of the positive electrode used as the counter electrode of the silicon-based negative electrode, which can solve the resistance problem of lithium secondary batteries, reduce the cracking in high-voltage batteries compared to the positive electrode using secondary particles alone, and also solve the problem of gas generation compared to the positive electrode using the single particle alone. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 A lithium secondary battery according to the present application is shown.

[0024] <Description of symbols>

[0025] 10: Negative electrode collector layer

[0026] 20: Negative electrode active material layer

[0027] 30: Diaphragm

[0028] 40: Positive electrode active material layer

[0029] 50: Positive electrode collector layer

[0030] 100: Negative electrode

[0031] 200: Positive DETAILED DESCRIPTION

[0032] Before describing the present invention, some terms are first defined.

[0033] Unless otherwise specifically described, in the present specification, when a component “includes,” “contains,” or “has” a constituent element, this does not mean to exclude other constituent elements but means that other constituent elements may further be included.

[0034] In this specification, “p to q” means a range of “p or more and q or less”.

[0035] In this specification, "specific surface area" is measured by the BET method, specifically, calculated from the nitrogen adsorption amount at liquid nitrogen temperature (77 K) by using BELSORP-mini II available from BEL Japan Co., Ltd. That is, in this application, the BET specific surface area may refer to the specific surface area measured by the above-mentioned measurement method.

[0036] In this specification, "Dn" means particle size distribution, and means the particle size at n% point in the cumulative distribution of the number of particles according to the particle size. That is, D50 is the particle size at 50% point in the cumulative distribution of the number of particles according to the particle size, D90 is the particle size at 90% point in the cumulative distribution of the number of particles according to the particle size, and D10 is the particle size at 10% point in the cumulative distribution of the number of particles according to the particle size. On the other hand, the particle size distribution can be measured using a laser diffraction method. Specifically, after the powder to be measured is dispersed in a dispersion medium, the resulting dispersion is introduced into a commercially available laser diffraction particle size measuring instrument (e.g., Microtrac S3500), wherein when the laser beam passes through the particle, the difference in the diffraction pattern according to the particle size is measured, and then the particle size distribution is calculated.

[0037] In the present specification, the description "a polymer contains a specific monomer as a monomer unit" means that the monomer participates in a polymerization reaction and is contained in the polymer as a repeating unit. In the present specification, when a polymer contains a monomer, this is interpreted as the same as the polymer containing the monomer as a monomer unit.

[0038] In the present specification, it should be understood that the term "polymer" is used in a broad sense including copolymers unless otherwise specified as a "homopolymer".

[0039] In this specification, the weight average molecular weight (Mw) and the number average molecular weight (Mn) are polystyrene conversion molecular weights measured by gel permeation chromatography (GPC) using commercially available monodisperse polystyrene polymers (standard samples) with various polymerization degrees for measuring molecular weight as standard materials. In this specification, unless otherwise specifically stated, molecular weight refers to weight average molecular weight.

[0040] The embodiments of the present invention will be described in detail below with reference to the accompanying drawings so that those skilled in the art can easily implement the present invention. However, the present invention can be implemented in various forms and is not limited to the following description.

[0041] An exemplary embodiment of the present specification provides a lithium secondary battery, comprising a positive electrode; a silicon-based negative electrode; a separator disposed between the positive electrode and the negative electrode; and an electrolyte, wherein the positive electrode comprises a positive electrode current collector layer and a positive electrode active material layer provided on one surface or both surfaces of the positive electrode current collector layer and containing a positive electrode active material layer composition, wherein the silicon-based negative electrode comprises a negative electrode current collector layer and a negative electrode active material layer provided on one surface or both surfaces of the negative electrode current collector layer and containing a negative electrode active material layer composition, wherein the negative electrode active material layer composition comprises a silicon-based active material, and the silicon-based active material comprises one or more selected from the group consisting of SiOx (x = 0), SiOx (0 < x < 2), SiC, and Si alloys, wherein the positive electrode active material layer composition comprises a positive electrode active material containing one or more selected from the group consisting of secondary particle positive electrode active materials and single particle positive electrode active materials, wherein the positive electrode active material comprises one or more selected from the group consisting of nickel, cobalt, manganese, and aluminum, and contains 50 mol% or more of nickel among all metals other than lithium, wherein based on 100 parts by weight of the positive electrode active material, the content of the single particle positive electrode active material is 1 part by weight or more and 50 parts by weight or less, and wherein the capacity loading of the positive electrode active material layer composition is 2 mAh / cm 2 or more and 5 mAh / cm 2 or less, and wherein based on 100 parts by weight of the silicon-based active material, the content of the single particle positive electrode active material is 0.01 part by weight or more and 4 parts by weight or less.

[0042] As the positive electrode, i.e., the counter electrode used in the present application, the lithium secondary battery according to the present application uses a mixture of the secondary particle positive electrode active material and the single particle positive electrode active material in the positive electrode and simultaneously adjusts the ratio of the single particle positive electrode active material. In particular, the secondary battery according to the present application is characterized in that the weight ratio of the silicon-based active material of the silicon-based negative electrode used as the counter electrode and the single particle positive electrode active material is adjusted compared to the capacity loading of the positive electrode active material layer composition.

[0043] Therefore, the main feature of the present application is to optimize the composition and content of the positive electrode used as the counter electrode of the silicon-based negative electrode, which can solve the resistance problem of the lithium secondary battery, reduce the cracking in the high-voltage battery compared to the case of using only the secondary particle positive electrode alone, and can also solve the problem of gas generation compared to the case of using only the single particle positive electrode alone.

[0044] Figure 1It is a diagram showing the stacked structure of a lithium secondary battery according to an exemplary embodiment of the present application. Specifically, the negative electrode 100 including the negative electrode active material layer 20 on one surface of the negative electrode current collector layer 10 can be seen, and the positive electrode 200 including the positive electrode active material layer 40 on one surface of the positive electrode current collector layer 50 can be seen. The negative electrode 100 and the positive electrode 200 for the lithium secondary battery are stacked with a separator 30 interposed therebetween.

[0045] The positive electrode, negative electrode, electrolyte, and separator included in the lithium secondary battery will be described separately below.

[0046] According to the present application, the silicon-based negative electrode may include a negative electrode current collector layer and a negative electrode active material layer provided on one surface or both surfaces of the negative electrode current collector layer and containing a negative electrode active material layer composition.

[0047] The thickness of the negative electrode current collector layer is generally 1 μm to 100 μm. There is no particular limitation on such a negative electrode current collector as long as it has high electrical conductivity and does not cause chemical changes in the battery. For example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, etc., aluminum cadmium alloy, etc. can be used. In addition, the negative electrode current collector layer may have micro-concavities and protrusions formed on the surface to enhance the adhesion to the negative electrode active material, and can be used in various different forms, such as a film, sheet, foil, net, porous body, foam body, or non-woven fabric body.

[0048] However, the thickness can be variously modified according to the type and use of the negative electrode used, and is not limited thereto.

[0049] In an exemplary embodiment of the present application, the negative electrode active material layer may include a negative electrode active material layer composition, and the negative electrode active material layer composition may include a silicon-based active material.

[0050] In an exemplary embodiment of the present application, the negative electrode active material layer may include a negative electrode active material layer composition, and the negative electrode active material layer composition may include one or more selected from the group consisting of a silicon-based active material, a negative electrode conductive material, and a negative electrode binder.

[0051] In an exemplary embodiment of the present application, the negative electrode active material layer may include a negative electrode active material layer composition, and the negative electrode active material layer composition may include a silicon-based active material, a negative electrode conductive material, and a negative electrode binder.

[0052] In an exemplary embodiment of the present application, the silicon-based active material may include one or more selected from the group consisting of SiOx (x = 0), SiOx (0 < x < 2), SiC, and Si alloy.

[0053] In an exemplary embodiment of the present application, the silicon-based active material may include one or more selected from the group consisting of SiOx (x = 0), SiOx (0 < x ≤ 2), and metal impurities, and based on 100 parts by weight of the silicon-based active material, may include 70 parts by weight or more of SiOx (x = 0).

[0054] In another exemplary embodiment, based on 100 parts by weight of the silicon-based active material, the content of SiOx (x = 0) may be 70 parts by weight or more, preferably 80 parts by weight or more, more preferably 90 parts by weight or more, and may be 100 parts by weight or less, preferably 99 parts by weight or less, more preferably 95 parts by weight or less.

[0055] In an exemplary embodiment of the present application, for the silicon-based active material, pure silicon (Si) may be particularly used as the silicon-based active material. Using pure silicon (Si) as the silicon-based active material may mean that, as described above, based on a total of 100 parts by weight of the silicon-based active material, it includes pure Si particles (SiOx (x = 0)) that are not combined with other particles or elements within the above range.

[0056] Note that the average particle size (D50) of the silicon-based active material of the present invention may be 5 μm to 10 μm, specifically 5.5 μm to 8 μm, more specifically 6 μm to 7 μm. If the average particle size is less than 5 μm, the specific surface area of the particles increases excessively, resulting in an excessive increase in the viscosity of the negative electrode slurry. As a result, the particles constituting the negative electrode slurry cannot be dispersed smoothly. In addition, if the size of the silicon-based active material is too small, the complex composed of the conductive material and the binder in the negative electrode slurry reduces the contact area between the silicon particles and the conductive material, increasing the possibility of disconnection of the conductive network, thereby reducing the capacity retention rate. On the other hand, if the average particle size is greater than 10 μm, there are overly large silicon particles, making the surface of the negative electrode uneven, resulting in uneven current density during charge and discharge. In addition, if the silicon particles are too large, the phase stability of the negative electrode slurry becomes unstable, deteriorating the processability. As a result, the capacity retention rate of the battery decreases.

[0057] In an exemplary embodiment of the present application, the silicon-based active material generally has a characteristic BET specific surface area. The BET specific surface area of the silicon-based active material is preferably 0.01 m 2 / g to 150.0 m 2 / g, more preferably 0.1 m 2 / g to 100.0 m 2 / g, particularly preferably 0.2 m 2 / g to 80.0 m2 / g, and most preferably 0.2 m 2 / g to 18.0 m 2 The BET specific surface area is measured according to DIN 66131 (using nitrogen).

[0058] In an exemplary embodiment of the present application, the silicon-based active material may be present, for example, in a crystalline or amorphous form, and is preferably not porous. The silicon particles are preferably spherical or fragmentary particles. Alternatively, but less preferably, the silicon particles may also have a fibrous structure or be present in the form of a silicon-containing film or coating.

[0059] In an exemplary embodiment of the present application, the content of the silicon-based active material may be 60 parts by weight or more based on 100 parts by weight of the negative electrode active material layer composition.

[0060] In another exemplary embodiment, based on 100 parts by weight of the negative electrode active material layer composition, the content of the silicon-based active material may be 60 parts by weight or more, preferably 65 parts by weight or more, more preferably 70 parts by weight or more, and may be 95 parts by weight or less, preferably 90 parts by weight or less, more preferably 80 parts by weight or less.

[0061] The negative electrode active material layer composition according to the present application uses a specific negative electrode conductive material and a negative electrode binder that can control the volume expansion rate during charge and discharge even when a significantly high capacity silicon-based active material is used within the above range. Therefore, even when the silicon-based active material is within the above range, the negative electrode active material layer composition does not deteriorate the performance of the negative electrode and has excellent output characteristics during charge and discharge.

[0062] In an exemplary embodiment of the present application, the silicon-based active material may have a non-spherical shape, and the sphericity (roundness) thereof is, for example, 0.9 or less, for example, 0.7 to 0.9, for example, 0.8 to 0.9, for example, 0.85 to 0.9.

[0063] In the present application, sphericity (roundness) is determined by the following Formula 1, where A is the area and P is the boundary line.

[0064] [Formula 1]

[0065] 4πA / P 2

[0066] In the related art, only graphite compounds are usually used as negative electrode active materials. However, in recent years, due to the increasing demand for high-capacity batteries, attempts to mix and use silicon-based compounds have increased in order to increase capacity. However, the silicon-based compounds are limited in that their volume expands rapidly during charge and discharge, resulting in damage to the conductive path formed in the negative electrode active material layer, thereby deteriorating the performance of the battery.

[0067] Therefore, in an exemplary embodiment of the present application, the negative electrode active material layer composition may include a negative electrode conductive material and a negative electrode binder. That is, the negative electrode conductive material plays a role in ensuring a conductive path, and the binder plays a role in retaining the negative electrode conductive material during charge and discharge.

[0068] In an exemplary embodiment of the present application, the negative electrode conductive material may include one or more selected from the group consisting of a point-shaped conductive material, a surface-shaped conductive material, and a line-shaped conductive material.

[0069] In an exemplary embodiment of the present application, the dot-shaped conductive material refers to a conductive material that can be used to improve the conductivity of the negative electrode, which forms conductivity without causing chemical changes and has a round or dot shape. Specifically, the dot-shaped conductive material can be one or more selected from the group consisting of natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, conductive fiber, fluorocarbon, aluminum powder, nickel powder, zinc oxide, potassium titanate, titanium oxide and polyphenylene derivatives, preferably including carbon black in terms of high conductivity and excellent dispersibility.

[0070] In an exemplary embodiment of the present application, the BET specific surface area of ​​the dot-shaped conductive material may be 40 m 2 / g and above 70 m 2 / g or less, preferably 45 m 2 / g and above 65 m 2 / g or less, more preferably 50 m 2 / g and above 60 m 2 / g or less.

[0071] In an exemplary embodiment of the present application, the particle size of the dot-shaped conductive material may be 10 nm to 100 nm, preferably 20 nm to 90 nm, and more preferably 40 nm to 60 nm.

[0072] In an exemplary embodiment of the present application, the conductive material may include a planar conductive material.

[0073] The planar conductive material refers to a conductive material that improves conductivity by increasing surface contact between silicon particles in the negative electrode and is used to suppress disconnection of conductive paths due to volume expansion. The planar conductive material may be a plate-shaped conductive material or a bulk-type conductive material.

[0074] In an exemplary embodiment of the present application, the planar conductive material may include one or more selected from the group consisting of plate-like graphite, graphene, graphene oxide, and graphite flakes, and may preferably be plate-like graphite.

[0075] In an exemplary embodiment of the present application, the average particle size (D50) of the planar conductive material may be 2 μm to 7 μm, specifically 3 μm to 6 μm, more specifically 4 μm to 5 μm. When the above range is met, sufficient particle size does not cause excessive increase in viscosity of the negative electrode slurry, resulting in easy dispersion. Therefore, when the same equipment and time are used for dispersion, the dispersion effect is excellent.

[0076] In an exemplary embodiment of the present application, a negative electrode composition is provided, in which the planar conductive material has a D10 of 0.5 μm to 1.5 μm, a D50 of 4.0 μm to 5.0 μm, and a D90 of 7.0 μm to 15.0 μm.

[0077] In an exemplary embodiment of the present application, as the planar conductive material, a high specific surface area planar conductive material having a high BET specific surface area or a low specific surface area planar conductive material may be used.

[0078] In an exemplary embodiment of the present application, for the planar conductive material, a planar conductive material with a high specific surface area or a planar conductive material with a low specific surface area can be used without limitation. However, in particular, the planar conductive material according to the present application may be affected to a certain extent by the dispersion effect in terms of electrode performance, so it is particularly preferred to use a planar conductive material with a low specific surface area that does not cause problems in terms of dispersion.

[0079] In an exemplary embodiment of the present application, the BET specific surface area of ​​the planar conductive material may be 1 m 2 / g or above.

[0080] In another exemplary embodiment, the BET specific surface area of ​​the planar conductive material may be 1 m 2 / g and above 500 m 2 / g or less, preferably 5 m 2 / g and above 300 m 2 / g or less, more preferably 5 m 2 / g and above 250 m 2 / g or less.

[0081] In another exemplary embodiment, the planar conductive material is a planar conductive material with a high specific surface area, and the BET specific surface area may satisfy 50 m 2 / g and above 500 m 2 / g or less, preferably 80 m 2 / g and above 300 m 2 / g or less, more preferably 100 m 2 / g and above 250 m 2 / g or less.

[0082] In another exemplary embodiment, the planar conductive material is a low specific surface area planar conductive material, and the BET specific surface area may satisfy 1 m 2 / g and above 40 m 2 / g or less, preferably 5 m 2 / g and above 30 m 2 / g or less, more preferably 5 m 2 / g and above 25 m 2 / g or less.

[0083] Other conductive materials may include linear conductive materials such as carbon nanotubes. The carbon nanotubes may be bundle-type carbon nanotubes. The bundle-type carbon nanotubes may contain a plurality of carbon nanotube units. Specifically, unless otherwise specified, the term "bundle-type" herein refers to a secondary shape in which a plurality of carbon nanotube units are arranged side by side or are wound in a bundle or rope-like manner so that the longitudinal axis orientation of the carbon nanotube units is substantially the same. The carbon nanotube unit has a cylindrical graphite sheet with a nanometer-sized diameter and has an sp2 bonding structure. In this case, depending on the curling angle and structure of the graphite sheet, the characteristics of a conductor or a semiconductor may be exhibited. Compared with the wound carbon nanotubes, the bundle-type carbon nanotubes can be more evenly dispersed during the manufacture of the negative electrode, and can more smoothly form a conductive network in the negative electrode, thereby improving the conductivity of the negative electrode.

[0084] In an exemplary embodiment of the present application, the negative electrode conductive material may include a linear conductive material, and the linear conductive material may be a carbon nanotube.

[0085] In an exemplary embodiment of the present application, the carbon nanotube may be SWCNT or / and MWCNT. When the linear conductive material is SWCNT, the length of the SWCNT may be 0.5 μm to 100 μm, preferably 1 μm to 80 μm.

[0086] In an exemplary embodiment of the present application, the content of the negative electrode conductive material may be 5 parts by weight or more and 40 parts by weight or less, based on 100 parts by weight of the negative electrode active material layer composition.

[0087] In another exemplary embodiment, the content of the negative electrode conductive material may be 5 parts by weight or more and 40 parts by weight or less, preferably 5 parts by weight or more and 30 parts by weight or less, and more preferably 5 parts by weight or more and 25 parts by weight or less, based on 100 parts by weight of the negative electrode active material layer composition.

[0088] In an exemplary embodiment of the present application, the negative electrode conductive material may include a planar conductive material and a linear conductive material, and a ratio of the planar conductive material to the linear conductive material may satisfy 1:0.001 to 1:0.3.

[0089] In an exemplary embodiment of the present application, since the negative electrode conductive material comprises the planar conductive material and the linear conductive material and respectively satisfies the above-mentioned composition and ratio, the life characteristics of the existing lithium secondary battery are not significantly affected, and the number of points at which the battery can be charged and discharged is increased, so that the output characteristics are excellent at a high C rate.

[0090] The composition of the negative electrode conductive material according to the present application is completely different from that of the conductive material used for the positive electrode. That is, the negative electrode conductive material according to the present application is used to maintain contact between the silicon-based active materials whose electrode volume expands greatly due to charge and discharge, while the positive electrode conductive material is used to provide a certain conductivity while playing a buffering role during rolling, and is completely different from the negative electrode conductive material of the present invention in terms of composition and function.

[0091] In addition, the negative electrode conductive material according to the present application is applied to the silicon-based active material, and its composition is completely different from that of the conductive material applied to the graphite-based active material. That is, since the conductive material used for the electrode with the graphite-based active material has only smaller particles than the active material, the conductive material has the characteristics of improving the output characteristics and imparting a certain conductivity, and is completely different from the negative electrode conductive material applied together with the silicon-based active material in the present invention in terms of composition and function.

[0092] In an exemplary embodiment of the present application, the structure and function of the plate-shaped conductive material used as the above-mentioned negative electrode conductive material are different from the structure and function of the carbon-based active material generally used as the negative electrode active material. Specifically, the carbon-based active material used as the negative electrode active material may be artificial graphite or natural graphite, and refers to a material processed into a spherical or dot-like shape for use to promote the storage and release of lithium ions.

[0093] On the other hand, the plate-like conductive material used as the negative electrode conductive material is a material having a planar or plate-like shape, and may be in the form of plate-like graphite. That is, the plate-like conductive material is a material contained in order to maintain a conductive path in the negative electrode active material layer, and refers to a material for securing a conductive path in a planar shape within the negative electrode active material layer, rather than a material for storing and releasing lithium.

[0094] That is, in the present application, using plate-like graphite as a conductive material means that graphite is processed into a planar or plate-like shape and used as a material that ensures a conductive path rather than a material that functions to store or release lithium. In this case, the negative electrode active material contained together has high capacity characteristics in terms of storing and releasing lithium, and is used to store and release all lithium ions transferred from the positive electrode.

[0095] On the other hand, in the present application, using a carbon-based active material as an active material means that the carbon-based active material is processed into a dot-like or spherical shape and used as a material for storing or releasing lithium.

[0096] In an exemplary embodiment of the present application, the negative electrode binder may include at least one selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, polyacrylic acid, and the above materials in which hydrogen is replaced by Li, Na, Ca, etc., and may also include various copolymers thereof.

[0097] The negative electrode binder according to an exemplary embodiment of the present application is used to retain the silicon-based active material and the negative electrode conductive material to prevent distortion and structural deformation of the negative electrode structure when the volume of the silicon-based active material expands and relaxes. When such a role is met, all conventional negative electrode binders can be applied. Specifically, an aqueous binder can be used, and more specifically, a PAM-based binder can be used.

[0098] In an exemplary embodiment of the present application, the content of the negative electrode binder may be 30 parts by weight or less, preferably 25 parts by weight or less, more preferably 20 parts by weight or less, and may be 5 parts by weight or more, 8 parts by weight or more, based on 100 parts by weight of the negative electrode active material layer composition.

[0099] Compared with the existing carbon-based negative electrode, when using a Si-based negative electrode, the aqueous binder is applied in the above-mentioned weight parts, so that a dot-shaped conductive material with a low functional group content can be used. In addition, the above-mentioned characteristics make the dot-shaped conductive material hydrophobic and make the bonding strength between the conductive material / binder excellent.

[0100] In an exemplary embodiment of the present application, the silicon-based negative electrode may be formed by coating a negative electrode slurry including the negative electrode active material layer composition on one surface or both surfaces of the negative electrode current collector layer.

[0101] In an exemplary embodiment of the present application, the negative electrode slurry may include a negative electrode active material layer composition and a slurry solvent.

[0102] In an exemplary embodiment of the present application, the solid content of the negative electrode slurry may satisfy a range of 5% or more and 40% or less.

[0103] In another exemplary embodiment, the solid content of the negative electrode slurry may satisfy a range of 5% to 40% both inclusive, preferably 7% to 35% both inclusive, and more preferably 10% to 30% both inclusive.

[0104] The solid content of the negative electrode slurry may mean the content of the negative electrode composition contained in the negative electrode slurry, and may mean the content of the negative electrode composition based on 100 parts by weight of the negative electrode slurry.

[0105] When the solid content of the negative electrode slurry satisfies the above range, the viscosity is appropriate during the formation of the negative electrode active material layer, so that the aggregation of particles of the negative electrode composition is minimized, thereby effectively forming the negative electrode active material layer.

[0106] In an exemplary embodiment of the present application, the slurry solvent may be used without limitation as long as it can disperse the negative electrode composition, and specifically, water or NMP may be used.

[0107] In an exemplary embodiment of the present application, the porosity of the negative electrode active material layer may satisfy a range of 10% or more and 60% or less.

[0108] In another exemplary embodiment, the porosity of the negative electrode active material layer may satisfy a range of 10% or more and 60% or less, preferably 20% or more and 50% or less, and more preferably 30% or more and 45% or less.

[0109] The porosity varies depending on the composition and content of the silicon-based active material, conductive material and binder contained in the negative electrode active material layer. In particular, when the silicon-based active material and conductive material according to the present application are contained in a specific composition and content, they satisfy the above-mentioned range, so that the electrode has conductivity and resistance within an appropriate range.

[0110] In an exemplary embodiment of the present application, the positive electrode includes a positive electrode collector layer and a positive electrode active material layer provided on one surface or both surfaces of the positive electrode collector layer and containing a positive electrode active material layer composition.

[0111] In an exemplary embodiment of the present application, the positive electrode active material layer may include a positive electrode active material layer composition, the positive electrode active material layer composition may include one or more selected from the group consisting of a positive electrode active material, a positive electrode conductive material and a positive electrode binder, and the positive electrode active material includes one or more selected from the group consisting of a secondary particle positive electrode active material and a single particle positive electrode active material.

[0112] In the positive electrode, there is no particular restriction on the positive electrode collector layer, as long as it has conductivity and does not cause chemical changes in the battery. For example, stainless steel, aluminum, nickel, titanium, calcined carbon, aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc., etc. can be used. In addition, the thickness of the positive electrode collector layer can generally be 1 to 500 μm, and the surface of the positive electrode collector layer can be formed with microscopic concave-convex to enhance the adhesion with the positive electrode active material. For example, the positive electrode collector layer can be used in various forms, such as films, sheets, foils, nets, porous bodies, foams, and non-woven fabrics.

[0113] In an exemplary embodiment of the present application, a lithium secondary battery is provided in which the thickness of the positive electrode collector layer and the negative electrode collector layer is 1 μm or more and 100 μm or less, and the thickness of the positive electrode active material layer and the negative electrode active material layer is 20 μm or more and 500 μm or less.

[0114] In an exemplary embodiment of the present application, the positive electrode active material may include one or more selected from the group consisting of secondary particle positive electrode active materials and single particle positive electrode active materials.

[0115] In another exemplary embodiment, the positive electrode active material may include a secondary particle positive electrode active material and a single particle positive electrode active material.

[0116] That is, the positive electrode active material according to the present application uses a mixed positive electrode active material of a secondary particle positive electrode active material and a single particle positive electrode active material.

[0117] The reaction potential of the silicon-based negative electrode is about 0.05 V higher than the reaction potential of the carbon-based negative electrode, so the silicon-based negative electrode is exposed to a high potential. If the secondary particle positive electrode active material is used alone, the problem of gas generation occurs again due to rupture under high voltage. Therefore, the application of single-particle positive electrode active materials as positive electrode active materials has been studied. However, if a single-particle positive electrode active material is used alone, the negative electrode no longer works due to the increased use of the bottom of the silicon-based negative electrode, resulting in poor cycle characteristics. Therefore, the present application includes both secondary particle positive electrode active materials and single particle positive electrode active materials.

[0118] In the lithium secondary battery according to the present application, as the positive electrode active material, a high Ni or medium Ni positive electrode active material containing one or more selected from the group consisting of nickel, cobalt, manganese and aluminum and containing 50 mol % or more of nickel in all metals except lithium is used. As a result, the problem of generating high temperature storage gas arises.

[0119] The lithium secondary battery according to the present application uses a mixed positive electrode active material of a secondary particle positive electrode active material and a single particle positive electrode active material and at the same time limits the ratio of the single particle positive electrode active material, so that high temperature gas can be reduced and cycle performance can be ensured.

[0120] In the present specification, the presence or absence of elements and the content of the elements in the positive electrode active material may be confirmed by ICP analysis, and the ICP analysis may be performed using an inductively coupled plasma atomic emission spectrometer (ICPAES, Perkin-Elmer 7300).

[0121] In the present specification, the single-particle positive electrode active material means the smallest particle unit distinguished as one agglomerate when observing a cross section of the positive electrode active material through a scanning electron microscope (SEM), and may be composed of one crystal grain or a plurality of crystal grains.

[0122] The method for forming the single-particle positive electrode active material is not particularly limited, but the single-particle positive electrode active material can generally be formed by over-firing at an elevated firing temperature, or can be manufactured by using an additive that facilitates over-firing, by changing the starting material, etc. Forming a single particle as described above enables improvement of thermal stability and suppression of side reactions and increase in resistance. The positive electrode active material in the form of a single-particle positive electrode active material can be formed, for example, by adding a lithium source such as LiOH and Li2CO3 to a composite transition metal hydroxide containing nickel, cobalt and manganese and mixing, and then over-firing the mixture at 800°C to 900°C for 10 to 25 hours under an oxygen atmosphere.

[0123] In an exemplary embodiment of the present application, the single particle is a term used to distinguish from the positive electrode active material particles in the form of secondary particles produced by the agglomeration of tens to hundreds of primary particles commonly used in the related field, and is a concept including single particles composed of one primary particle and agglomerated particles of less than 10 primary particles.

[0124] In an exemplary embodiment of the present application, the secondary particle cathode active material is the same as described above, and may be the same as the single particle cathode active material in terms of kind, but may mean a form in which the single particle cathode active material is aggregated.

[0125] In an exemplary embodiment of the present application, the single-particle positive electrode active material may be in the form of a single particle of a commonly used positive electrode active material.

[0126] In an exemplary embodiment of the present application, the single-particle positive electrode active material includes one or more selected from the group consisting of nickel, cobalt, manganese and aluminum, contains more than 50 mol % of nickel in all metals except lithium, and has no H2-H3 phase transition at a voltage of 4.0 V or more.

[0127] In an exemplary embodiment of the present application, the single-particle positive active material has no H2-H3 phase transition at a voltage above 4.0 V. That is, various adjustment factors are included, but if the content of Ni included together satisfies a value below a specific range, the above-mentioned phase transition is not observed. In other words, generally, when a single-particle active material is used, the effect of reducing gas generation is large, but in the high-voltage phase change interval of the positive electrode, the negative electrode side reaction increases, resulting in rapid deterioration of the cycle performance, thereby deteriorating the performance of the lithium secondary battery. However, in particular, by using a single-particle positive active material that does not undergo a specific phase change at a high voltage (above 4.0 V) as a medium Ni single-particle positive active material, the cycle performance can be ensured while reducing gas generation.

[0128] In an exemplary embodiment of the present application, the single-particle positive electrode active material has no H2-H3 phase transition at a voltage of 4.0 V or more. In this case, the physical property of the single-particle positive electrode active material may mean a physical property having the following characteristics: after manufacturing a half-cell including the single-particle positive electrode active material, no phase transition is caused when a voltage of 4.0 V or more is applied to the half-cell.

[0129] In an exemplary embodiment of the present application, a lithium secondary battery is provided, in which, when an electrochemical capacity result is obtained by charging a positive electrode half cell containing the single-particle positive electrode active material to 4.3 V at a constant current and differentiating the electrochemical capacity result with respect to voltage, the single-particle positive electrode active material has no peak value that is more than 1.5 times the average value in the voltage range of 4.0 V to 4.3 V.

[0130] In particular, in the case of a conventional single-particle positive electrode material, when an electrochemical capacity result is obtained by charging a positive electrode half cell to 4.3 V at a constant current and differentiating the electrochemical capacity result with respect to voltage, a peak is observed in the voltage range of 4.0 V to 4.3 V. However, the single-particle positive electrode active material as described above does not observe a peak in the above range, which enables the gas reduction effect to be achieved while also ensuring the cycle performance.

[0131] In an exemplary embodiment of the present application, the average particle size (D50) of the single-particle positive electrode active material may be 1 μm to 10 μm, preferably 2 μm to 7 μm. That is, the single-particle positive electrode active material may include a small particle form.

[0132] In an exemplary embodiment of the present application, the secondary particle positive active material may include a large particle form and a small particle form in a bimodal form, and the average particle size (D50) of the secondary particle positive active material may be 5 μm to 20 μm, preferably 7 μm to 15 μm.

[0133] In an exemplary embodiment of the present application, there is provided a lithium secondary battery in which the average particle diameter (D50) of the positive electrode active material is 1 μm or more and 20 μm or less.

[0134] The average particle size of the positive electrode active material corresponds to the overall average particle size including the above-mentioned single-particle positive electrode active material and secondary-particle positive electrode active material.

[0135] In an exemplary embodiment of the present application, the following lithium secondary battery is provided, in which, based on 100 parts by weight of the positive electrode active material, the content of the single-particle positive electrode active material is greater than 1 part by weight and less than 50 parts by weight, and the content of the secondary particle positive electrode active material is greater than 50 parts by weight and less than 99 parts by weight.

[0136] In an exemplary embodiment of the present application, the content of the single-particle positive electrode active material may be 1 part by weight or more and 50 parts by weight or less based on 100 parts by weight of the positive electrode active material.

[0137] In another exemplary embodiment, the content of the single-particle positive electrode active material may be 1 part by weight or more and 50 parts by weight or less, preferably 5 parts by weight or more and 50 parts by weight or less, and more preferably 15 parts by weight or more and 50 parts by weight or less, based on 100 parts by weight of the positive electrode active material.

[0138] In an exemplary embodiment of the present application, based on 100 parts by weight of the positive electrode active material, the content of the secondary particle positive electrode active material may be 50 parts by weight or more and 99 parts by weight or less, preferably 50 parts by weight or more and 95 parts by weight or less, and more preferably 50 parts by weight or more and 85 parts by weight or less.

[0139] As described above, the positive electrode according to the present application uses a mixed positive electrode material of secondary particles and single particles, which has the characteristic of reducing the high-temperature storage gas generated from the positive electrode material. If the single-particle positive electrode active material according to the present application is used beyond the above range, the high-temperature storage gas can be reduced, but the cycle performance is deteriorated, resulting in a rapid decrease in life characteristics.

[0140] The positive electrode active material according to the present application is characterized in that the ratio of the single particles and the secondary particles is adjusted as described above, and the weight portion of the silicon-based active material for the counter electrode is also adjusted.

[0141] That is, in an exemplary embodiment of the present application, a lithium secondary battery is provided, in which the capacity loading of the positive electrode active material layer composition is 2 mAh / cm 2 Above and 5 mAh / cm 2 Below, and the content of the single-particle positive electrode active material is 0.01 parts by weight or more and 4 parts by weight or less based on 100 parts by weight of the silicon-based active material.

[0142] In another exemplary embodiment, the capacity loading of the positive electrode active material layer composition may be 2 mAh / cm 2 Above and 5 mAh / cm 2 Below, and based on 100 parts by weight of the silicon-based active material, the content of the single-particle positive electrode active material may be 0.01 parts by weight or more and 4 parts by weight or less, preferably 0.03 parts by weight or more and 3.9 parts by weight or less.

[0143] As described above, based on the capacity loading of the positive electrode, the silicon-based active material contains the single-particle positive electrode active material as described above relative to 100 parts by weight. Adjusting the weight ratio of the single-particle positive electrode active material in the positive electrode active material alone as described above cannot solve the life characteristics problem caused by the volume expansion of the silicon-based negative electrode (especially pure Si) used as the counter electrode. However, adjusting the ratio of the single-particle positive electrode active material relative to the silicon-based active material as described above makes it possible to provide a lithium secondary battery with reduced gas generation and particularly excellent life characteristics, which is the main purpose of the present invention.

[0144] In an exemplary embodiment of the present application, a lithium secondary battery is provided, in which the single-particle positive electrode active material and the secondary particle positive electrode active material include a material selected from the group consisting of LiNi x Co y Mn z O2 (x+y+z=1), LiNi a Co b Mn c Al d O2 (a+b+c+d=1), LiMn2O4, LiNi 0.5 Mn 1.5 O2 and LiM x Fe y One or more of the group consisting of PO4 (M: transition metal, x+y=1).

[0145] In an exemplary embodiment of the present application, the following lithium secondary battery is provided, in which the single-particle positive electrode active material and the secondary particle positive electrode active material are nickel cobalt manganese (NCM) oxide or nickel cobalt manganese aluminum (NCMA) oxide, and the content of nickel contained in all metals other than lithium in the nickel cobalt manganese (NCM) oxide and the nickel cobalt manganese aluminum (NCMA) oxide is 50 mol% or more.

[0146] In another exemplary embodiment, the single-particle positive electrode active material and the secondary particle positive electrode active material may be nickel cobalt manganese (NCM) oxide or nickel cobalt manganese aluminum (NCMA) oxide, and the nickel cobalt manganese (NCM) oxide and the nickel cobalt manganese aluminum (NCMA) oxide, the content of nickel contained in all metals except lithium may be 50 mol % or more, preferably 55 mol % or more, more preferably 58 mol % or more, and most preferably 60 mol % or more. In addition, based on all metals except lithium, the content of nickel (Ni) may be 99 mol % or less or 95 mol % or less.

[0147] When the content of nickel is lower than the above range, the content of cobalt is increased to increase the thermal stability. However, the capacity of the positive electrode active material is reduced, resulting in the problem that the positive electrode active material cannot be applied to an electrochemical device that requires a high capacity.

[0148] On the other hand, since the content of nickel is high within the above range, the lithium secondary battery containing the same can exhibit high capacity characteristics. However, as the content of nickel increases, the content of cobalt and / or manganese relatively decreases. Therefore, the thermal stability may be reduced. Therefore, when the content of nickel is within the above range, the efficiency of the lithium secondary battery according to the present application can be maximized.

[0149] In an exemplary embodiment of the present application, the nickel-cobalt-manganese (NCM) oxide can be expressed as the following lithium nickel cobalt manganese oxide. The lithium nickel cobalt manganese (NCM) oxide is composed of Li 1+x (Ni a Co b Mn c )O2 (0.97 ≤ x ≤ 1.06, 0 < a < 1, 0 < b < 1, 0 < c < 1, a + b + c = 1), the Ni-Co-Mn ternary system positive electrode active material represented by Li 1+x (Ni a Co b Mn c )O4 (0.97 ≤ x ≤ 1.06, 0 < a < 2, 0 < b < 2, 0 < c < 2, a + b + c = 2), or a mixture thereof, and is a composite integrating the high capacity of nickel-containing oxides, the thermal stability of manganese-containing oxides, and the excellent electrochemical characteristics of cobalt-containing oxides and other characteristics. The lithium nickel cobalt manganese (NCM) oxide can be doped with a small amount of metal elements to an extent that meets the object of the present invention. For example, as a non-limiting example, the lithium nickel cobalt manganese (NCM) oxide represented by Li 1+x (Ni a Co b Mn c )O2 (0.97 ≤ x ≤ 1.06, 0 < a < 1, 0 < b < 1, 0 < c < 1, a + b + c = 1) or Li 1+x (Ni a Co b Mn c )O4 (0.97 ≤ x ≤ 1.06, 0 < a < 2, 0 < b < 2, 0 < c < 2, a + b + c = 2) can each independently be doped with one or more metals selected from the group consisting of Na, K, Mg, Ca, Sr, Ni, Co, Ti, Al, Si, Sn, Mn, Cr, Fe, V, and Zr.

[0150] The amount of metal doped into the lithium nickel cobalt manganese (NCM) can be within a range that does not significantly increase the cathode resistance. For example, based on each element, the doped metal in the lithium nickel cobalt manganese (NCM) oxide can be in the range of 10 to 1500 ppm, 50 to 1000 ppm, or 100 to 500 ppm, but is not limited thereto. As a non-limiting example, the lithium nickel cobalt manganese (NCM) oxide generally uses 2 to 3 elements as the doped metal, and based on each element, the doped metal can be present in an amount of several hundred ppm.

[0151] In an exemplary embodiment of the present application, in the nickel cobalt manganese (NCM) oxide, the content of nickel contained in all metals except lithium can be 50 mol% or more, specifically 55 mol% or more, more specifically 58 mol% or more, and more specifically 60 mol% or more.

[0152] In Li 1+x (Ni a Co b Mn C )O2 (0.97 ≤ x ≤ 1.06, 0 < a < 1, 0 < b < 1, 0 < c < 1, a + b + c = 1), the content of nickel can mean the ratio of a contained. That is, in the case of a three-component system, it can mean the ratio of nickel among nickel, cobalt, and manganese metals.

[0153] In an exemplary embodiment of the present application, the nickel cobalt manganese aluminum (NCMA) oxide can be represented as the following lithium nickel cobalt manganese aluminum oxide. The nickel cobalt manganese aluminum (NCMA) oxide is a Ni-Co-Mn-Al four-component cathode active material represented by Li 1+x (Ni a Co b Mn C Al d )O2 (0.97 ≤ x ≤ 1.06, 0 < a < 1, 0 < b < 1, 0 < c < 1, 0 < d < 1, a + b + c + d = 1), a Ni-Co-Mn-Al four-component cathode active material represented by Li 1+x (Ni a Co b Mn C Al d )O4 (0.97 ≤ x ≤ 1.06, 0 < a < 2, 0 < b < 2, 0 < c < 2, 0 < d < 2, a + b + c + d = 2), or a mixture thereof, and is a composite that combines the characteristics such as the high capacity of nickel-containing oxides, the thermal stability of manganese-containing oxides, and the excellent electrochemical characteristics of cobalt-containing oxides. The lithium nickel cobalt manganese aluminum (NCMA) oxide can be doped with a small amount of metal elements to an extent that meets the purpose of the present invention.

[0154] For example, as a non-limiting example, by Li 1+x (Ni a Co b Mn c Al d )O2 (0.97 ≤ x ≤ 1.06, 0 < a < 1, 0 < b < 1, 0 < c < 1, 0 < d < 1, a + b + c + d = 1) or Li 1+x (Ni a Co b Mn c Al d )O4 (0.97 ≤ x ≤ 1.06, 0 < a < 2, 0 < b < 2, 0 < c < 2, 0 < d < 2, a + b + c + d = 2), the lithium nickel cobalt manganese aluminum (NCMA) represented by the positive electrode active material of the Ni-Co-Mn-Al four-component system can be independently doped with one or more metals selected from the group consisting of Na, K, Mg, Ca, Sr, Ni, Co, Ti, Al, Si, Sn, Mn, Cr, Fe, V, and Zr.

[0155] In an exemplary embodiment of the present application, in the nickel cobalt manganese aluminum (NCMA) oxide, the content of nickel contained in all metals except lithium can be 80 mol% or more, specifically 85 mol% or more, more specifically 88 mol% or more, and more specifically 93 mol% or more.

[0156] In the formula represented by Li 1+x (Ni a Co b Mn c Al d )O2 (0.97 ≤ x ≤ 1.06, 0 < a < 1, 0 < b < 1, 0 < c < 1, 0 < d < 1, a + b + c + d = 1), the content of nickel can mean the ratio of a contained. That is, in the case of a four-component system, the content of nickel can mean the ratio of nickel among nickel, cobalt, manganese, and aluminum metals.

[0157] In an exemplary embodiment of the present application, the following lithium secondary battery is provided. In the lithium secondary battery, based on 100 parts by weight of the positive electrode active material layer composition, the content of the positive electrode active material is 90 parts by weight or more.

[0158] In another exemplary embodiment, based on 100 parts by weight of the positive electrode active material layer composition, the content of the positive electrode active material can be 90 parts by weight or more, preferably 93 parts by weight or more, more preferably 95 parts by weight or more, and can be 99 parts by weight or less or 98 parts by weight or less.

[0159] The positive electrode active material layer may further include a positive electrode conductive material and a positive electrode binder in addition to the positive electrode active material.

[0160] In this case, the positive electrode conductive material is used to impart conductivity to the electrode, and can be used without particular limitation, as long as the positive electrode conductive material has electronic conductivity without causing chemical changes in the battery to be constituted. Specific examples may include graphite, such as natural graphite and artificial graphite; carbon-based materials, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powder or metal fiber, such as copper, nickel, aluminum, and silver; conductive whiskers, such as zinc oxide and potassium titanate; conductive metal oxides, such as titanium oxide; or conductive polymers, such as polyphenylene derivatives, and the like, and any one of them or a mixture of two or more thereof may be used.

[0161] Specifically, in one embodiment of the present application, the following lithium secondary battery is provided, in which the positive electrode conductive material comprises single-walled carbon nanotubes (SWCNTs) or multi-walled carbon nanotubes (MWCNTs), and the content is greater than 0.1 parts by weight and less than 2 parts by weight based on 100 parts by weight of the positive electrode active material layer composition.

[0162] In another exemplary embodiment, the content of the positive electrode conductive material may be 0.1 parts by weight or more and 2 parts by weight or less, preferably 0.3 parts by weight or more and 1.5 parts by weight or less, and more preferably 0.5 parts by weight or more and 1.2 parts by weight or less, based on 100 parts by weight of the positive electrode active material layer composition.

[0163] In addition, the positive electrode binder is used to improve the bonding between the positive electrode active material particles and the adhesion between the positive electrode active material and the positive electrode collector. Specific examples may include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, or various copolymers thereof, and any one of them or a mixture of two or more thereof may be used.

[0164] In this case, the content of the positive electrode binder may be 0.1 parts by weight or more and 10 parts by weight or less, preferably 1 part by weight or more and 5 parts by weight or less, based on 100 parts by weight of the positive electrode composition.

[0165] The diaphragm is used to separate the negative electrode from the positive electrode and provide a migration path for lithium ions, wherein any diaphragm can be used as the diaphragm without particular limitation, as long as it is commonly used in secondary batteries, in particular, it is preferred to use a diaphragm with high moisture retention capacity for electrolytes and low resistance to electrolyte ion migration. Specifically, a porous polymer film can be used, for example, a porous polymer film made of polyolefin-based polymers such as ethylene homopolymers, propylene homopolymers, ethylene / butene copolymers, ethylene / hexene copolymers and ethylene / methacrylate copolymers, or a laminated structure of more than two layers thereof. In addition, a common porous non-woven fabric can be used, such as a non-woven fabric formed of high melting point glass fiber, polyethylene terephthalate fiber, etc. In addition, a coated diaphragm comprising a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength, and a diaphragm with a single-layer or multilayer structure can be selectively used.

[0166] In the present application, examples of the electrolyte may include an organic liquid electrolyte, an inorganic liquid electrolyte, a solid polymer electrolyte, a gel-type polymer electrolyte, a solid inorganic electrolyte, or a molten inorganic electrolyte that can be used to manufacture the lithium secondary battery, but are not limited thereto.

[0167] Specifically, the electrolyte may include a nonaqueous organic solvent and a metal salt.

[0168] As the nonaqueous organic solvent, for example, an aprotic organic solvent such as N-methyl-2-pyrrolidone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, dioxolane derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ether, methyl propionate or ethyl propionate can be used.

[0169] Especially, in carbonate system organic solvent, ethylene carbonate and propylene carbonate as cyclic carbonate are high viscosity organic solvents, and because their dielectric constant is high, thus dissociate lithium salt well, therefore can preferably use.When described cyclic carbonate and low viscosity and low dielectric constant linear carbonate such as dimethyl carbonate and diethyl carbonate are mixed with suitable ratio and used, can prepare the electrolyte with high conductivity, so such combination use can be more preferred.

[0170] As the metal salt, a lithium salt which is a material easily soluble in the non-aqueous electrolyte can be used, and for example, a material selected from F - , Cl - ,I- 、NO3 - 、N(CN) 2- 、BF4 - 、ClO4 - PF6 - 、(CF3)2PF4 - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF - 、(CF3)6P - CF3SO3 - CF3CF2SO3 - 、(CF3SO2)2N - 、(FSO2)2N - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - 、(SF5)3C - 、(CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - 、CH3CO2 - 、SCN - and (CF3CF2SO2)2N - One or more substances from the group consisting of are used as anions of the lithium salt.

[0171] In order to improve the life characteristics of the battery, inhibit the decline in battery capacity, improve the discharge capacity of the battery, etc., in addition to the above-mentioned electrolyte components, the electrolyte may also contain one or more additives, such as halogenated alkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, n-glycol dimethyl ether, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol or aluminum chloride.

[0172] An exemplary embodiment of the present invention provides a battery module including the secondary battery as a unit cell, and a battery pack including the battery module. Since the battery module and the battery pack include secondary batteries having high capacity, high rate performance, and high cycle characteristics, the battery module and the battery pack can be used as a power source for medium and large devices selected from the group consisting of electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and power storage systems.

[0173] Invention Mode

[0174] Hereinafter, preferred embodiments will be provided in order to better understand the present invention. It is obvious to those skilled in the art that the embodiments are provided only to illustrate the present invention, and various modifications and changes can be made within the scope and technical spirit of the present invention. Such modifications and changes naturally fall within the scope of the claims contained herein.

[0175] <Production Example>

[0176] (1) Manufacturing of positive electrode

[0177] The positive electrode active material, positive electrode conductive material (LB. CNT) and binder (PVdF, KF9700) in Table 1 below were added to a solvent (N-methylpyrrolidone, NMP) at a weight ratio of 97.0:1.56:1.44 to prepare a positive electrode slurry. The positive electrode slurry was applied to an aluminum (Al) film having a thickness of 12 μm as a positive electrode collector, dried, and then rolled to prepare a positive electrode. In this case, the capacity loading of the positive electrode is shown in Table 1 below.

[0178]

[0179] In the above Table 1, parts by weight of the single-particle positive electrode active material and the secondary-particle positive electrode active material are shown based on 100 parts by weight of the entire positive electrode active material.

[0180] In Table 1 above, single particle A is a Li(Ni)-containing NCMA in which the NCMA other than lithium (Li) and oxygen (O2) has a ratio of Ni:Co:Mn:Al=86:5:8:1. a Co b Mn c Al d )O2, which satisfies the ratio (a:b:c:d=0.86:0.05:0.08:0.01).

[0181] In the above Table 1, secondary particle A is a Li(Ni)-containing NCMA in which NCMA other than lithium (Li) and oxygen (O2) has a ratio of Ni:Co:Mn:Al=86:5:7:2. a Co b Mn c Al d )O2, which satisfies the ratio (a:b:c:d=0.86:0.05:0.07:0.02).

[0182] In the above Table 1, single particle B is a Li (Ni) in which NCM (A) other than lithium (Li) and oxygen (O2) has a ratio of Ni:Co:Mn=86:8:6. a Co b Mn c)O2, which satisfies the ratio (a:b:c=0.86:0.08:0.06).

[0183] In the above Table 1, single particle C is a Li (Ni) single particle positive electrode active material in which NCM other than lithium (Li) and oxygen (O2) has a ratio of Ni:Co:Mn=60:20:20. a Co b Mn c )O2, which satisfies the ratio (a:b:c=0.60:0.20:0.20). In this case, in the case of single particle C, it was confirmed that no H2-H3 phase transition was observed, and when the electrochemical capacity result was obtained by charging the positive electrode half cell containing single particle C to 4.3 V at a constant current and differentiating the electrochemical capacity result with respect to the voltage, there was no peak of more than 1.5 times the average value in the voltage range of 4.0 V to 4.3 V.

[0184] (2) Manufacturing of negative electrode

[0185] A negative electrode active material layer composition was prepared using Si (average particle size (D50): 5 μm) as a silicon-based active material, a first conductive material, a second conductive material, and polyacrylamide as a binder at a weight ratio of 80:9.6:0.4:10. A negative electrode slurry (solid concentration: 28 wt %) was prepared by adding the composition to distilled water as a solvent for forming a negative electrode slurry.

[0186] The first conductive material is plate-like graphite (specific surface area: 17 m 2 / g, average particle size (D50): 3.5 μm), and the second conductive material is carbon nanotubes.

[0187] As a mixing method, the slurry was prepared by dispersing the first conductive material, the second conductive material, the binder, and water at 2500 rpm for 30 minutes using a homomixer, adding the active material thereto, and dispersing the resulting mixture at 2500 rpm for 30 minutes.

[0188] The negative electrode slurry was prepared at 3.00 mg / cm 2 A loading amount of 200 Å was coated on both surfaces of a copper current collector (thickness: 8 μm) serving as a negative electrode current collector, which was then roll-pressed and dried in a vacuum oven at 130° C. for 10 hours to form a negative electrode active material layer (thickness: 23 μm).

[0189] (3) Manufacturing of secondary batteries

[0190] The electrode assembly was manufactured by inserting a compression-resistant thin film separator (PE, 12 μm) having a 4 μm / 4 μm ceramic coating between the positive electrode and the negative electrode. After the electrode assembly was placed in a case, an electrolyte was injected into the case, thereby manufacturing a lithium secondary battery.

[0191] Experimental Example 1: Lifespan Evaluation

[0192] For the lithium secondary battery including the negative electrode manufactured in the embodiment and the comparative example, the life and capacity retention rate were evaluated using an electrochemical charge and discharge device. The secondary battery was subjected to an in-situ cycle test at 4.2-3.27 V, 1 C / 1 C, during which 0.33 C / 0.33 C charge and discharge (4.2-3.11 V) was performed every 120 cycles to measure the capacity retention rate, and the results are listed in Table 2.

[0193] Capacity retention rate (%) = {(discharge capacity at the Nth cycle) / (discharge capacity at the first cycle)} × 100

[0194] Experimental Example 2: Measurement and Evaluation of Resistance Increase Rate

[0195] In Experimental Example 1, during the test, after measuring the capacity retention rate by charging and discharging the battery at 0.33 C / 0.33 C every 120 cycles (4.2-3.11 V), the resistance was measured by discharging the battery at a pulse of 2.5 C at SOC 50, and then the resistance increase rate was compared and analyzed. The results are shown in Table 2 below.

[0196] Experimental Example 3: Evaluation of the amount of gas generated by a fully charged positive electrode

[0197] After fully charging the 1 Ah cells manufactured in Examples and Comparative Examples, the cells were stored in an oven at 60° C. for 8 weeks. Then, the amount of gas generation was confirmed and compared using a gas chromatography (GC) method, and the results are shown in Table 2 below.

[0198]

[0199] As can be seen from Tables 1 and 2 above, it can be confirmed that the lithium secondary battery according to the present application in which the above-mentioned single-particle positive electrode active material is applied to the positive electrode can reduce the amount of gas generated, and the higher the content of the single-particle positive electrode active material, the more the gas generation is reduced. However, it can be confirmed that the higher the blending ratio of the single-particle positive electrode active material, the worse the cycle performance, and when the content of the single-particle positive electrode active material exceeds a certain content as in Comparative Examples 1 and 2, the life performance deteriorates rapidly. In addition, with the same subject matter as Comparative Example 1, in the case of Comparative Example 3 in which the content of the single-particle positive electrode active material is lower than the scope of the present application, it can be confirmed that the gas generation is large and the cycle performance is deteriorated.

Claims

1. A lithium secondary battery comprising: positive electrode; Silicon-based negative electrode; a separator disposed between the positive electrode and the negative electrode; and Electrolytes, wherein the positive electrode comprises a positive electrode current collector layer and a positive electrode active material layer provided on one surface or both surfaces of the positive electrode current collector layer and containing a positive electrode active material layer composition, The silicon-based negative electrode comprises a negative electrode current collector layer and a negative electrode active material layer provided on one surface or both surfaces of the negative electrode current collector layer and containing a negative electrode active material layer composition, wherein the negative electrode active material layer composition contains a silicon-based active material, and the silicon-based active material contains one or more selected from the group consisting of SiO x (x = 0), SiO x (0 < x < 2), SiC, and Si alloys, wherein the positive electrode active material layer composition comprises one or more positive electrode active materials selected from the group consisting of secondary particle positive electrode active materials and single particle positive electrode active materials, wherein the positive electrode active material comprises one or more selected from the group consisting of nickel, cobalt, manganese and aluminum, and contains 50 mol % or more of nickel in all metals except lithium, wherein the content of the single-particle positive electrode active material is greater than or equal to 1 part by weight and less than or equal to 50 parts by weight based on 100 parts by weight of the positive electrode active material, The capacity loading of the positive electrode active material layer composition is 2 mAh / cm 2 Above and 5 mAh / cm 2 The following, and The content of the single-particle positive electrode active material is 0.01 parts by weight or more and 4 parts by weight or less based on 100 parts by weight of the silicon-based active material.

2. The lithium secondary battery according to claim 1, wherein the silicon-based active material contains one or more selected from the group consisting of SiO x (x = 0), SiO x (0 < x < 2), and metal impurities, and based on 100 parts by weight of the silicon-based active material, contains 70 parts by weight or more of SiO x (x = 0). 3 . The lithium secondary battery according to claim 1 , wherein the content of the silicon-based active material is 60 parts by weight or more based on 100 parts by weight of the negative electrode active material layer composition.

4. The lithium secondary battery according to claim 1, wherein the single-particle positive electrode active material and the secondary particle positive electrode active material include a material selected from the group consisting of LiNi x Co y Mn z O2 (x+y+z=1), LiNi a Co b Mn c Al d O2 (a+b+c+d=1), LiMn2O4, LiNi 0.5 Mn 1.5 O2 and LiM x Fe y One or more of the group consisting of PO4 (M: transition metal, x+y=1).

5. The lithium secondary battery according to claim 1, wherein the single particle positive electrode active material and the secondary particle positive electrode active material are nickel cobalt manganese (NCM) oxide or nickel cobalt manganese aluminum (NCMA) oxide, and The nickel-cobalt-manganese (NCM) oxide and the nickel-cobalt-manganese-aluminum (NCMA) oxide contain nickel in an amount of 50 mol % or more among all metals except lithium. 6 . The lithium secondary battery according to claim 1 , wherein an average particle diameter (D50) of the positive electrode active material is 1 μm or more and 20 μm or less. 7 . The lithium secondary battery according to claim 1 , wherein the content of the positive electrode active material is 90 parts by weight or more based on 100 parts by weight of the positive electrode active material layer composition.

8. The lithium secondary battery according to claim 1, wherein the content of the single-particle positive electrode active material is 1 part by weight or more and 50 parts by weight or less, and the content of the secondary particle positive electrode active material is 50 parts by weight or more and 99 parts by weight or less, based on 100 parts by weight of the positive electrode active material.

9. The lithium secondary battery according to claim 1, wherein the thickness of the positive electrode current collector layer and the negative electrode current collector layer is each 1 μm or more and 100 μm or less, and The thickness of the positive electrode active material layer and the negative electrode active material layer is each 20 μm or more and 500 μm or less. 10 . The lithium secondary battery according to claim 1 , wherein the single-particle positive electrode active material has no H2-H3 phase transition at a voltage of 4.0 V or more.

11. The lithium secondary battery according to claim 1, wherein when an electrochemical capacity result is obtained by charging a positive electrode half cell containing the single-particle positive electrode active material to 4.3 V at a constant current and differentiating the electrochemical capacity result with respect to voltage, the single-particle positive electrode active material has no peak value that is more than 1.5 times the average value in the voltage range of 4.0 V to 4.3 V.

Citation Information

Patent Citations

  • Anode for lithium ion battery

    JP2009080971A